2020
DOI: 10.12688/f1000research.25413.2
|View full text |Cite
|
Sign up to set email alerts
|

Biocuration - mapping resources and needs

Abstract: Background: Biocuration involves a variety of teams and individuals across the globe. However, they may not self-identify as biocurators, as they may be unaware of biocuration as a career path or because biocuration is only part of their role. The lack of a clear, up-to-date profile of biocuration creates challenges for organisations like ELIXIR, the ISB and GOBLET to systematically support biocurators and for biocurators themselves to develop their own careers. Therefore, the ELIXIR Training Platform launched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…Despite its importance, the contribution and effort of biocurators are extremely difficult to attribute and quantify ( 5 ). This is relevant for all categories of curators irrespective of them being professional curators, volunteer curators or just experts that occasionally provide feedback on existing annotation records.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its importance, the contribution and effort of biocurators are extremely difficult to attribute and quantify ( 5 ). This is relevant for all categories of curators irrespective of them being professional curators, volunteer curators or just experts that occasionally provide feedback on existing annotation records.…”
Section: Introductionmentioning
confidence: 99%
“…This is relevant for all categories of curators irrespective of them being professional curators, volunteer curators or just experts that occasionally provide feedback on existing annotation records. The European life science infrastructure for biological information (ELIXIR, https://elixir-europe.org/ ), the International Society for Biocuration (ISB, https://www.biocuration.org ) ( 6 ) and the Global Organization for Bioinformatics Learning, Education and Training (GOBLET, https://www.mygoblet.org ) ( 7 , 8 ) recognized the need to ensure that the role of biocurator is visible and valued ( 5 ). According to a global survey, they found that biocurators have diverse job titles, are highly skilled, perform a variety of activities and use a wide range of tools and resources.…”
Section: Introductionmentioning
confidence: 99%
“…According to a global survey they found that biocurators have diverse job titles, are highly skilled, perform a variety of activities and use a wide range of tools and resources. But the majority of biocurators are unaware of this as a career, or simply think that biocuration is not the main aspect of their job (5) . An established strategy for crediting curators is to offer co-authorship in the article describing the corresponding curated database.…”
Section: Introductionmentioning
confidence: 99%
“…Even though in principle expert curation scales well with the growth of scientific literature, it is highly demanding, requiring the allocation of dedicated resources and time (3,4). Despite its importance, the contribution and effort of biocurators is extremely difficult to acknowledge and quantify (5). This is relevant for all categories of curators irrespective of they being professional curators, volunteer curators or just experts which occasionally provides feedback on existing annotation records.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation